A well-defined poly(vinyl benzoxazine) obtained by selective free radical polymerization of vinyl group in bifunctional benzoxazine monomer. (15th January 2016) - Liu, Ying-Xuan; Ma, He-Ming; Liu, Yun; Qiu, Jin-Jun; Liu, Cheng-Mei
Abstract: Abstract: A heterobifunctional monomer, namely, 3-(4-ethenylphenyl)-3, 4-dihydro-2H-1, 3-benzoxazine (VBOZN), which contains both vinyl group and benzoxazine group, was successfully prepared by three-step method with high purity and satisfactory yield. The chemical structure of VBOZN was identified by NMR, FTIR and elemental analysis. VBOZN selectively underwent free radical polymerization initiated by azodiisobutyronitrile to obtain homopolymer P(VBOZN) with Mn 4960 and Mw 11700. The benzoxazine-containing linear P(VBOZN) has Tg about 112 °C and shows better thermal stability than that of polystyrene. The P(VBOZN) was cured by heating without any catalyst and the peak temperature assigned to cationic ring-opening polymerization of P(VBOZN) centered at 244 °C. The molecular weight of P(VBOZN)could be improved dramatically by copolymerization of VBOZO with N-phenylmaleimide. Both homopolymer and copolymers show high stability and theoretical limiting oxygen index are near 30. P(VBOZN) and copolymers are not only new kinds of well-defined multifunction polymers with the potential of postpolymerization and/or chemical modification, they are also novel intrinsic fire retarded polymers. Graphical abstract: Highlights: Vinyl benzoxazine (VBOZN), a heterobifunctional monomer, was successfully prepared. Functional P(VBOZN) was obtained by selectively polymerizing the double bond. P(VBOZN) can be regarded as a novel green and intrinsic fire retarded polymers. The molecular weight of P(VBOZN) can be improved by copolymerization with electron-deficient monomers. P(VBOZN) has the potential to be a "real" thermoplastic thermoset.